2022
DOI: 10.3390/jcm11174953
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Gestational Diabetes and Its Risk Factors: Pregnancy Outcome of Women with Gestational Diabetes Risk Factors According to Glycose Tolerance Test Results

Abstract: Background: Gestational diabetes mellitus (GDM) can cause maternal and neonatal health problems, and its prevalence is increasing worldwide. We assessed the screening of GDM during a 7-year period and compared the outcome of pregnancies at high risk for GDM. Methods: We analyzed non-selected pregnant women (n = 5021) receiving antenatal care in Tartu University Hospital, Estonia in 2012–2018. Pregnant women were classified based on the absence or presence of GDM risk factors as low risk (n = 2302) or high risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A retrospective study done in Estonia, where risk-based screening is practiced, showed that women with risk factors for GDM who screened negative with OGTT were still at risk of excessive weight gain and large for gestational age (LGA) deliveries, which are in turn associated with adverse pregnancy outcomes [ 15 ]. This may be explained by the confounding effect of other risk factors such as obesity on LGA and excessive weight gain and implies that women with risk factors for GDM who screen negative should not be dismissed and should still be provided with management options for reducing gestational weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study done in Estonia, where risk-based screening is practiced, showed that women with risk factors for GDM who screened negative with OGTT were still at risk of excessive weight gain and large for gestational age (LGA) deliveries, which are in turn associated with adverse pregnancy outcomes [ 15 ]. This may be explained by the confounding effect of other risk factors such as obesity on LGA and excessive weight gain and implies that women with risk factors for GDM who screen negative should not be dismissed and should still be provided with management options for reducing gestational weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Out of 240 cases, 0.2% of GDM were macrosomic and in IGT 0.085 were macrosomic. According to Hansen et al (2014), 18 the proportion of newborns that were large for gestational age (LGA), which is defined as birth weight >2 SDs above the mean for gestation and sex, was strongly and independently correlated with IGT during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…There are several factors predisposing to GDM, with advanced maternal age ( ≥ 35 years), maternal obesity (body mass index ≥ 30 kg/m 2 ) and history of GDM in previous pregnancy being the most prominent [ 3 ]. Moreover, weight gain during pregnancy, family history of diabetes, polycystic ovary syndrome (PCOS), ethnicity (Asian, Asian American, African American, Native American, Pacific Islander, Latin), and achievement of pregnancy with Assisted Reproductive Technologies (ART) have been associated with GDM development [ 4 , 5 ]. Cigarette smoking is a considerable threat to public health in both developed and developing countries, associated with all the leading causes of death [ 6 ].…”
Section: Introductionmentioning
confidence: 99%